2021
DOI: 10.3390/polym13234080
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, Development, and Scaling-Up of Poly(lactic acid) (PLA) Biocomposites with Hazelnuts Shell Powder (HSP)

Abstract: In this work, two different typologies of hazelnuts shell powders (HSPs) having different granulometric distributions were melt-compounded into poly(lactic acid) (PLA) matrix. Different HSPs concentration (from 20 up to 40 wt.%) were investigated with the aim to obtain final biocomposites with a high filler quantity, acceptable mechanical properties, and good melt fluidity in order to be processable. For the best composition, the scale-up in a semi-industrial extruder was then explored. Good results were achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Augustin-Salazar et al confirmed the degradation effect of nutshell on polyesters reporting that the onset of thermal degradation in PLA-based biocomposites with pecan nutshells assume the lowest values if mixed with the holocellulosic fraction in respect to the lignin or the whole nutshell [73]. Moreover, despite that the HSPs were dried before extrusion, some residual humidity could be also present in the hygroscopic cellulosic material [59].…”
Section: Melt Flow Analysismentioning
confidence: 92%
See 2 more Smart Citations
“…Augustin-Salazar et al confirmed the degradation effect of nutshell on polyesters reporting that the onset of thermal degradation in PLA-based biocomposites with pecan nutshells assume the lowest values if mixed with the holocellulosic fraction in respect to the lignin or the whole nutshell [73]. Moreover, despite that the HSPs were dried before extrusion, some residual humidity could be also present in the hygroscopic cellulosic material [59].…”
Section: Melt Flow Analysismentioning
confidence: 92%
“…Comparing the effect of the coarser HSP (F2) in respect to the finest one (F3), it was shown a lower torque value for the finest HSP. This result can be explained considering that HSPs induces into the polymeric matrix some chain scission caused by the reactions between their surface groups (mainly hydroxyl groups on holocellulose component) or the humidity content with biopolyesters [47,59,71]. In fact, it was reported that the hydrolytic scission of ester bond of PLA and its composites was mainly caused by the diffusion of water in the amorphous region and the presence of -OH groups [72].…”
Section: Melt Flow Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Hazelnut shell (HS) powder was provided by Agrindustria Tecco (Agrindustria Tecco, Cuneo, Italy) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…They reported that ELO had a dual role as a coupling agent and/or a plasticizer, but overall, it improved the overall performance of the PLA/HS composite. Similarly, Aliotta et al [ 30 ] used analytical models to evaluate the effect of powder size and adhesion between HS and the PLA matrix. In addition, they reported interesting results for scaled-up composites.…”
Section: Introductionmentioning
confidence: 99%